COMPARATIVE BODY WEIGHT AND MORPHOMETRIC TRAITS OF WEST AFRICAN DWARF AND RED SOKOTO GOATS IN SOUTH WEST, NIGERIA - Ajayi, Bababunmi Alaba; Babatunde, Olatunji; Akintunde, Adeyinka Oye; Atoyebi, Gbemiga Oyewole (FUDMA JOURNAL OF SCIENCES, 2025)
A total of 633 goats were sampled randomly across three states in Southwestern Nigeria for comparation of morphometric traits between West African Dwarf (WAD) and Red Sokoto (RS). Data collected were analysed using multivariate analyses of linear body measurements. The study aimed at confirming regional representation, intra- and inter-breed variations, and validating phenotypic indicators of genetic diversity. Twenty-two morphometric measurements were taken on each goat. RS goats were superior (P < 0.05) to the WAD in body weight and body proportions, except for ear width (male and female), ear length, canon circumference, and udder circumference (female only), where both breeds were comparable. The two breeds exhibited distinct morphometric profiles, as reflected in their respective loadings on the principal components. Five principal components (PCs) were similarly extracted for both breeds, but with different percentage contributions for each PC. In WAD the highest component loadings were Heart Girth, Body Depth and Chest Depth conversely it was Rump Height, Wither Height, Ear Length and Head Length in RS. The Mahalanobis distance between WAD and RS goats was 37.52 (overall), indicating a high level of breed divergence thus high heterotic potential from crossbreeding. These values reflect noticeable variations in physical features that are influenced by both sex and breed. Cluster analysis confirmed the relative importance of each morphometric trait across breed and sex. The backward stepwise Discriminant Function Analysis (DFA) highlighted the traits most relevant for differentiating between WAD and RS goats. There is significant difference between the two breeds to support crossbreeding gains.